Formation of digital competence of CS bachelors in the use of cloud-based learning environments - Tetiana Vakaliuk; Oleg Spirin; Valerii Kontsedailo (Academy of Cognitive and Natural Sciences, 2021)
The article clarifies the concept of digital competence of CS bachelors in the use of cloud-based learning environments. The criteria (value-motivational, cognitive, operational-activity, research, didactic), indicators, and levels (low, medium, sufficient, high) of the formation of digital competence of CS bachelors in the use of cloud-based learning environments (CBLE) are specified. The results of the pedagogical experiment were analyzed, demonstrating an increased level of digital competence formation of CS bachelors in the use of CBLE, and thus the pedagogical efficiency of adopting the methodical system of using CBLE in the training of CS bachelors.